Structural and Intermediary Social Determinants of Health and the Emotional and Behavioral Health of US Children - Ngozi V. Enelamah; Margaret Lombe; Mansoo Yu; Melissa L. Villodas; Andrew Foell; Chrisann Newransky; Lisa C. Smith; Von Nebbitt (MDPI AG, 2023)
Children grow up in homes where varying environmental and socioeconomic contexts have a bearing on their emotional and behavioral health (EBH). This study used data from a representative sample of the child supplement of the US National Health Information Survey (NHIS) and applied the social determinants of health (SDoH) framework to explore factors associated with child EBH. We conducted a path analysis of the child's EBH measured by the strengths and difficulties questionnaire (SDQ) from their macro and socioeconomic contexts, e.g., policy, household, and other health system risk factors. For children in the sample, aged 4 to 17 years old (n = 9205), most path relationships to child SDQ scores were statistically significant. The total effects from a child's visit to a mental health specialist (0.28) and child's age (0.22) had the highest coefficients to child SDQ scores. A modified model showed a better fit with X2 (4) = 22.124, RMSEA = 0.021, and 90% CI [0.013-0.03], CFI = 0.98. Findings indicate that child factors such as being older, the use of mental healthcare services, and family socioeconomic status were significantly associated with EBH, calling attention to the need for more responsive policy and behavioral health interventions that address household/familial and child-level factors, critical determinants of child wellbeing.